2019
DOI: 10.1007/s10151-019-02048-0
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fluorescence angiography for intra-operative assessment of pedicled omentoplasty for filling of a pelvic cavity: a pilot study

Abstract: BackgroundDuring creation of a pedicled omentoplasty, blood flow to segments of the omentum might become compromised. If unrecognized, this can lead to omental necrosis. The purpose of this study was to investigate the potential added intra-operative value of the use of fluorescence angiography (FA) with indocyanine green (ICG) to assess omental perfusion.MethodsAll consecutive patients undergoing a pedicled omentoplasty in a 6-month period (April 1 2018–October 1 2018) in a University hospital were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The percentage of intra-operative detection of partial omental ischaemia by conventional assessment (17% and 12% in the two cohorts, respectively) corresponds to reported rates in the literature [14]. In the cohort with FA, resection of ischaemic parts of the omentoplasty was performed according to FA findings in an additional 78%, which is in line with the observation from a previous pilot study [8].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The percentage of intra-operative detection of partial omental ischaemia by conventional assessment (17% and 12% in the two cohorts, respectively) corresponds to reported rates in the literature [14]. In the cohort with FA, resection of ischaemic parts of the omentoplasty was performed according to FA findings in an additional 78%, which is in line with the observation from a previous pilot study [8].…”
Section: Discussionsupporting
confidence: 88%
“…After conventional white light assessment of omental perfusion, the decision was made whether or not there was a need for partial omental resection due to ischaemia. From April 2018 onwards, FA was subsequently performed as previously described [8]. FA interpretation was based on the near infrared image (standard setting) and was a consensus between two colorectal surgeons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 1894 patients showed that omentoplasty did not reduce the risk of postoperative presacral abscesses or perineal complications [93]. ICG fluorescence angiography of the transferred omentum was recently assessed in a pilot study [94]. Remarkably, ICG fluorescence angiography led to a change in surgical management in 80% of the patients.…”
Section: Omentoplastic Perfusionmentioning
confidence: 99%
“…Omentoplasty is a well-known method to fill the pelvic cavity after APR or in case of complications after rectal cancer surgery. A pilot study of the intraoperative value of NIR fluorescence imaging with ICG to assess omental perfusion after the creation of a pedicled omentoplasty found that a change in decision making occurred in 80% of the cases[ 110 ], and a positive impact on the nonhealing rates of patients undergoing salvage surgery for chronic pelvic sepsis was also observed[ 111 ].…”
Section: Other Usesmentioning
confidence: 99%